The dressmaker of Khair Khana [compact disc, unabridged] : five sisters, one remarkable family, and the woman who risked everything to keep them safe - Lemmon, Gayle Tzemach (Dreamscape Media, 2011)
When the Taliban took control of Kabul, Kamila Sidiqi and all the women of Kabul saw their lives transformed: Overnight they were banned from schools and offices and even leaving their front door on their own. Desperate to help her family and support her five brothers and sisters at home, Kamila began sewing clothes in her living room. Little did she know then that the tailoring venture she started to help her siblings would be the beginning of a dressmaking business.